Meninjau etika akuntan publik dalam filosofi singo mengkok - Putri , Diana; Afanillah, Hafif; Dwi Rahmawati, Linda (JAE (JURNAL AKUNTANSI DAN EKONOMI), 2023)
The aim of this research is to internalize the ethics of public accountants singo mengkok's Philosophy which is known to be full of the meaning of the philosophy of life. This research uses a literature study method that examines scientific articles. The main Findings is internalization of public accounting ethics singo mengkok‘s philosophy creates a context for applying code of public accounting ethics profession in carrying out their professional services by always remember that all their behavior will be accounted to God, so they must be able to restrain their passions and balance with faith and sincerity. Singo Mengkok is a symbol of noble teachings with elements so that the internalization of public accounting ethics in the philosophy of Singo Mengkok becomes a new solution in accounting science, also become a strategy for public accountants to avoid ethical violations that have occurred.